Research groups in Brazil and the breastfeeding subject - Michelle Araújo Moreira; Regina Lúcia Mendonça Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This present essay is about a quantitative research whose subject is the featuring of the research groups in Brazil, in relation to the connection between woman health and breastfeeding. The purpose was to identify the existing research groups that had breastfeeding as focus of interest, acting on woman health area. From November 2004 to July 2005, a survey based on the census of the National Scientific and Technologic Council from Brazilian Directory, was made by research groups. Using the descriptors woman health and breastfeeding, 12 groups were identified. The survey showed that the distribution of the groups for period was the following: 25% in the 80's, 50% in the 90's and 25 % in 2000. In relation to the institutional instance, 58% corresponded to federal institutions, 25% to the state and 17% to the private ones. Among the federative units, 345 of the groups are in São Paulo, 26% in Rio de Janeiro and 8% distributed among Pernambuco, Alagoas, Bahia, Rio Grande do Sul and Sergipe. In relation to the quantitative of researchers, 42% of the groups had 1 to 5, 425 6 to 10, 8% 11 to 20, and 8% more than 20. In relation to the quantitative of students, 25% of the groups had 0 to 5, 50% 6 to 10, 8,3% 11 to 20 and 18,7 more than 20. In relation to the top number of techniques, 84% had 0 to5, 8% 11 to 20 and 8% more than 20. About the number of research lines, 67% has 1 to 5, 25% 6 to 10, 8% 11 to 20. About the linking of the groups to the instruction units or department, it's shown the following distribution: 25% not specified, 16,9% to social medicine and 8,3% distributed among the departments of Toco-gynecology, Nursery, Maternal-Childish and Psychiatric, Education, Pediatrics, Technologic Institute and research, Milk Bank and sector of Pharmacology and Conduct / Behavior. Analyzing the focus, 37% emphasized Collective Health , 27% Children Health, 8% Biology, 8% Woman Health, 7% Adult Health, 5% Mental Health, 3% Dental Health, and 2% Education. The conclusion is: there is scarcity of Research Groups about breastfeeding; after all, the woman health hasn't had exclusive attention, with the predominance of the children health. KEY WORDS: Breastfeeding, Woman Health.